Intra-seasonal variability of the DWBC in the western subpolar North Atlantic. (March 2015) - Fischer, J.; Karstensen, J.; Zantopp, R.; Visbeck, M.; Biastoch, A.; Behrens, E.; Böning, C.W.; Quadfasel, D.; Jochumsen, K.; Valdimarsson, H.; Jónsson, S.; Bacon, S.; et al.
Highlights: A joint analysis of deep current meter records in the western North Atlantic. Intra-seasonal variability dominates the deep boundary current. Topographic waves near 10 d periods trapped over steep topography. Basin centers are showing longer periods (50 d) caused by the eddy field. Observed variability characteristics compared to high resolution model simulation. Abstract: The Deep Western Boundary Current (DWBC) along the western margin of the subpolar North Atlantic is an important component of the deep limb of the Meridional Overturning near its northern origins. A network of moored arrays from Denmark Strait to the tail of the Grand Banks has been installed for almost two decades to observe the boundary currents and transports of North Atlantic Deep Water as part of an internationally coordinated observatory for the Atlantic Meridional Overturning Circulation. The dominant variability in all of the moored velocity time series is in the week-to-month period range. While the temporal characteristics of this variability change only gradually between Denmark Strait and Flemish Cap, a broad band of longer term variability is present farther along the path of the DWBC at the Grand Banks and in the interior basins (Labrador and Irminger Seas). The vigorous intra-seasonal variability may well mask possible interannual to decadal variability that is typically an order of magnitude smaller than the high-frequency fluctuations. Here, the intra-seasonal variability is quantified at key positions along the DWBC path using both, observations and high resolution model data. The results are used to evaluate the model circulation, and in turn the model is used to relate the discrete measurements to the overall pattern of the subpolar circulation. Topographic waves are found to be trapped by the steep topography all around the western basins, the Labrador and Irminger Seas. In the Labrador Sea, the high intra-seasonal variability of the boundary current regime is separated by a region of extremely low variability in narrow recirculation cells from the basin interior. There, the variability is also on intra-seasonal time scales, but at much longer periods around 50 days.